A MODEST COMMEMORATIVE TREE - THE PRIMARY SCHOOL MAGAZINE AND THE BRAZIL'S CENTENNIAL INDEPENDENCE. (SANTA CATARINA, 1922) - Philippi, Carolina Cechella [UNESP] (FapUNIFESP (SciELO), 2023)
This article analyses on the publication of Santa Catarina's Primary Education Magazine (1922), paying attention to the narrative mechanisms and the instructions for the organization of the school materiality in Brazil Independent's centenary. As its objectives, aims to question the ways in which the magazine presented facts, citations, and references to build the necessary legitimacy for the Public Instruction Directory activities, headed by Henrique da Silva Fontes. In addition, the aim of this article was also to understand the way that the Primary Education Magazine provided subsidies for the teaching daily practice in primary school. In conclusion, notes the disputes tracked through the guidelines provided in the publication, as well as the narrative effort to enter Santa Catarina's history and public instruction in a national situation of combat against illiteracy.
UNE MODESTE ARBRE COMMÉMORATIVE - LE REVUE DE L'ENSEIGNEMENT PRIMAIRE ET LE CENTENAIRE DE L'INDÉPENDANCE (SANTA CATARINA, 1922)
“UMA MODESTA ÁRVORE COMEMORATIVA” – A REVISTA DE ENSINO PRIMÁRIO E O CENTENÁRIO DA INDEPENDÊNCIA NACIONAL (SANTA CATARINA, 1922)
Keywords: Educational journal; History of Education; Teaching profession